Edukasi Pencegahan Stunting dan Kesehatan Gigi dengan Prinsip Hifdzun Nasl - Abrori, abrori; Praptawati, Destary (CV. Agrapana Media, 2026)
Stunting and children's dental health problems are still public health challenges, although their prevalence shows a downward trend nationally and regionally. Data shows that the prevalence of Stunting nationally is 19.8% and Central Java is 17.1%, while the problem of pediatric dental caries in Indonesia is still high. In RW IV Meteseh Village, Tembalang District, the limitations of posyandu cadres and variations in the level of community education have the potential to hinder promotive and preventive efforts. This community service activity aims to increase public knowledge and awareness about Stunting prevention and children's dental health through education based on Hifdzun Nasl principles. Community service uses a community-based participatory education (CBPE) approach, which is a participatory education approach that places the community as the main subject in the learning process and changes in health behavior with a pre-test and post-test design on 52 residents from three RTs. The activity involved lecturers, nursing and English education students, community leaders, and RW administrators. Educational materials include Stunting, 1,000 HPK, breastfeeding and MP-ASI, PHBS, dental health for toddlers, and the integration of Hifdzun Nasl values. The results showed a significant increase in participants' knowledge with an average score difference of 30.5 points and an N-Gain value of 0.63 (medium-high category). The highest improvement was found in the understanding of Hifdzun Nasl's values, which strengthened the acceptance of health messages. Field findings also show that there are still toddlers at risk of Stunting and dental caries problems, confirming the urgency of value-based educational interventions. Hifdzun Nasl's principles-based health education is effective in increasing public knowledge and awareness and has the potential to encourage sustainable changes in parenting behavior.